Linguistic Identity Positioning in Facebook Posts During Second Language Study Abroad: One Teen’s Language Use, Experience, and Awareness - Dressler, Roswita; Dressler, Anja (Canadian Journal of Applied Linguistics, 2016)
Abstract Teens who post on the popular social networking site Facebook in their home environment often continue to do so on second language study abroad sojourns. These sojourners use Facebook to document and make sense of their experiences in the host culture and position themselves with respect to language(s) and culture(s). This study examined one teen’s identity positioning through her Facebook posts from two separate study abroad experiences in Germany. Data sources included her Facebook posts from both sojourns and a written reflection completed upon return from the second sojourn. Findings revealed that this teen used Facebook posts to position herself as a German-English bilingual and a member of an imagined community of German-English bilinguals by making a choice on which language(s) to use, reporting her linguistic successes and challenges, and indicating growing language awareness. This study addresses the call by study abroad researchers (Coleman, 2013; Kinginger, 2009, 2013; Mitchell, Tracy-Ventura, & McManus, 2015) to investigate the effects of social media, such as Facebook, as part of the contemporary culture of study abroad, and sheds light on the role it plays, especially regarding second language identity positioning. Résumé Les adolescents qui affichent sur le site social Facebook dans leur environnement familial continuent à le faire pendant leur séjour à l’étranger. Ces adolescents utilisent Facebook pour documenter et réfléchir sur leurs expériences dans le pays hôte et pour se positionner par rapport à leur langue et à leur culture ou aux langues et aux cultures. Cette étude a examiné le positionnement d’une adolescente par rapport à son identité à travers des messages Facebook lors de deux séjours différents en Allemagne. Les données de ces expériences incluent des messages Facebook provenant des deux séjours et une réflexion écrite complétée à son retour du deuxième séjour. Les résultats ont révélé que cette adolescente a utilisé les messages Facebook pour se positionner en tant que bilingue allemand-anglais. De plus, elle a démontré faire partie d’une communauté imaginée de bilingues allemand-anglais en choisissant une langue spécifique selon le contexte et en rapportant les succès et défis linguistiques qu’elle a vécus. Elle a également démontré un certain éveil aux langues. Cette étude comble les besoins d’étudier l’usage des médias sociaux tels que Facebook et le rôle du positionnement identitaire des adolescents qui font des séjours à l’étranger. Ces besoins ont été démontrés par des chercheurs qui travaillent dans le domaine (Coleman, 2013 ; Kinginger, 2009, 2013 ; Mitchell, Tracy-Ventura et McManus, 2015). L’usage des médias sociaux tels que Facebook et le rôle qu’ils ont à positionner l’identité linguistique des adolescents qui étudient à l’étranger sera le thème de cet article.